2012
DOI: 10.4049/jimmunol.1103426
|View full text |Cite
|
Sign up to set email alerts
|

Defining GM-CSF– and Macrophage-CSF–Dependent Macrophage Responses by In Vitro Models

Abstract: GM-CSF and M-CSF (CSF-1) induce different phenotypic changes in macrophage lineage populations. The nature, extent, and generality of these differences were assessed by comparing the responses to these CSFs, either alone or in combination, in various human and murine macrophage lineage populations. The differences between the respective global gene expression profiles of macrophages, derived from human monocytes by GM-CSF or M-CSF, were compared with the differences between the respective profiles for macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
418
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(455 citation statements)
references
References 53 publications
32
418
0
5
Order By: Relevance
“…However, growth factors such as M-CSF and granulocyte/macrophage CSF (GM-CSF) induce distinct phenotypic changes in macrophage populations (Lacey et al, 2012). Recent work indicated that M-CSF increases SR-A expression in primary macrophages via p38 MAP kinase activation (Nikolic et al, 2011).…”
Section: Induction Of Mdms Without Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, growth factors such as M-CSF and granulocyte/macrophage CSF (GM-CSF) induce distinct phenotypic changes in macrophage populations (Lacey et al, 2012). Recent work indicated that M-CSF increases SR-A expression in primary macrophages via p38 MAP kinase activation (Nikolic et al, 2011).…”
Section: Induction Of Mdms Without Growth Factorsmentioning
confidence: 99%
“…We confirmed that SR-A expression was frequently detected in AcLDL-loaded MDMs generated by our new method (Figure 2D We showed that MDMs can be induced by coculture with autologous non-adherent PBMCs without adding any growth factors (Figure 2). Recently, controversial issues have been raised concerning the nature of macrophages induced in vitro by growth factors such as M-CSF and GM-CSF (Fleetwood et al, 2007;Lacey et al, 2012). Also, recent work indicates that treatment with M-CSF up-regulates SR-A expression in macrophages (Nikolic et al, 2011).…”
Section: Mdms Loaded With Acldl Express Mica/bmentioning
confidence: 99%
“…Mouse bone marrow-derived macrophages (BMM) and human monocytederived macrophages (MDM) were prepared as before (50). Briefly, bone marrow cells from the femurs of mice were cultured in RPMI 1640 medium supplemented with 10% FCS, 2 mM GlutaMax-1, 100 U/ml penicillin, and 100 mg/ml streptomycin in the presence of M-CSF (CSF-1; 2000 U/ml).…”
Section: Preparation Of Mouse Bone Marrow-derived Macrophages and Hummentioning
confidence: 99%
“…On day 7, adherent cells were harvested. Human monocytes were purified from buffy coats (Red Cross Blood Bank, Melbourne, VIC, Australia) and MDM generated as before from M-CSF-treated cultures (50). Peritoneal exudate cells were elicited by i.p.…”
Section: Preparation Of Mouse Bone Marrow-derived Macrophages and Hummentioning
confidence: 99%
“…They also promote angiogenesis, tissue remodeling and wound healing. 2,3 Macrophages are plastic cells. Their phenotype and functions can be modulated, depending on their microenvironment.…”
Section: Introductionmentioning
confidence: 99%